Estado nutricional infantil y estilos educativos familiares : apreciación de expertos (2013)
ABSTRACT: Childhood obesity has been studied from aspects related with diagnosis and treatment, primarily. However, studies related with prevention from no genetics family factors have been largely absent from the focus of research in public health and nutrition. Objective: To know nutrition professional perceptions about a possible relationship between type of family, the nutritional status of children and parental educational styles. Materials and methods: A descriptive and exploratory study. A semi-structured online questionnaire was applied to professionals from Spain, Chile, Portugal and Colombia. The questionnaire included three variables: type of family, parental educational styles and parent reported nutritional status of children. Results: Regardless family type, parental educational style was associated with nutritional children status as follow: A protective style with overweight, and a democratic style with normal nutritional status. Authoritarian and neglectful styles were associated with malnutrition by excess or deficit (p <0.05). Conclusion: Theses results may be useful as base for new research about the relationships between childhood obesity and family environment.